Biogenic Synthesis of Cu-Doped ZnO Photocatalyst for the Removal of Organic Dye - Biruktait Ayele Lemecho; Fedlu Kedir Sabir; Dinsefa Mensur Andoshe; Noto Susanto Gultom; Dong-Hau Kuo; Xiaoyun Chen; Endale Mulugeta; Temesgen D. Desissa; Osman Ahmed Zelekew (Bioinorganic Chemistry and Applications)
The Cu-doped ZnO photocatalysts were prepared with a green and coprecipitation approach by using water hyacinth (Eichhornia crassipes) aquatic plant extract. In the preparation process, different amount of copper precursors such as 1, 2, 3, 4, and 5% of molar ratio were added to zinc nitrate precursors and abbreviated as Cu-ZnO (1%), Cu-ZnO (2%), Cu-ZnO (3%), Cu-ZnO (4%), and Cu-ZnO (5%), respectively. The characterization of the obtained samples was carried out, and the removal of the methylene blue (MB) dye was examined. Out of all catalysts, Cu-ZnO (3%) had the best photocatalytic performance and 89% of the MB dye was degraded. However, the degradation performances of blank (without catalysts), ZnO, Cu-ZnO (1%), Cu-ZnO (2%), Cu-ZnO (4%), and Cu-ZnO (5%) catalysts were 6, 54, 69, 83, 80, and 73%, respectively. Therefore, the use of water hyacinth plant extract with the optimum amount of Cu added to ZnO during the preparation of the catalyst could have a promising application in the degradation of organic pollutants.